Studies on production of peptide antibiotic by thermotolerant Bacillus sp. - D, Joshi R; S, Hamde V; M, Umrikar A; Kulkarni, S S; A, Bhate M (International Multidisciplinary Research Journal, 2012)
The soil sample was collected and screened for isolation of higher antibiotic producing bacterial strain. The isolated bacterial strain was tentatively identified as Bacillus sp. by biochemical characters using Bergey’s manual. The present study is focused on the optimization of different parameters for production of peptide antibiotic (Bacitracin) using synthetic medium. The antibacterial activity of isolate was analyzed against S. aureus. The nutritional ingredients for bacitracin production were found as glucose (1%) and L-glutamic acid (0.5 %) as carbon and nitrogen source respectively. The prominent bacitracin production was obtained after 48 hrs incubation at 40°C temperature and at 7 pH.